2018
DOI: 10.1007/s00726-018-2553-3
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation induces long-term beneficial effects on glucose homeostasis in ob/ob mice

Abstract: The sulfur-containing amino acid, taurine (Tau), regulates glucose and lipid homeostasis under normal, pre- and diabetic conditions. Here, we aimed to verify whether Tau supplementation exerts its beneficial effects against obesity, hyperglycemia and alterations in islet functions, in leptin-deficient obese (ob/ob), over a long period of treatment. From weaning until 12 months of age, female ob/ob mice received, or not, 5% Tau in drinking water (obTau group). After this period, a reduction in hypertriglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
0
26
0
1
Order By: Relevance
“…Other studies showed that taurine protected islets and hepatocytes against lipotoxicity induced by the infusion of oleate or fatty acids [29,30]. Borck et al [31] noticed that 5% taurine solution given to obese mice with drinking water for 12 months decreased TAG and improved glucose tolerance and insulin sensitivity. In another study conducted by this team, 2.5% TAU solution given to hypothalamic obese rats for a shorter period (130 days) did not affect the fasting glucose level, but decreased the insulin and TAG concentration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that taurine protected islets and hepatocytes against lipotoxicity induced by the infusion of oleate or fatty acids [29,30]. Borck et al [31] noticed that 5% taurine solution given to obese mice with drinking water for 12 months decreased TAG and improved glucose tolerance and insulin sensitivity. In another study conducted by this team, 2.5% TAU solution given to hypothalamic obese rats for a shorter period (130 days) did not affect the fasting glucose level, but decreased the insulin and TAG concentration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 12 papers were selected for inclusion in this systematic review. [27][28][29][30][31][32][33][34][35][36][37][38] Currently, two clinical trials are also ongoing which their results have not been yet published. 39,40 A flowchart of the process of studies selection has been summarized in Figure 1.…”
Section: Analysis Of the Datamentioning
confidence: 99%
“…Majority of the animal studies used spontaneous model of T2DM including Otsuka Long-Evans Tokushima fatty (OLETF) rats, 28,30,31,33 GK rats, 29 and ob/ob rats. 34 Two studies induced diabetes by high fat and high sugar diet combined with streptozotocin (STZ) 32 and feeding the genetically hyperglycemic KK mice a high calorie diet. 27 Of the 8 animal articles identified, 7 articles included measures of blood glucose, [27][28][29][30][32][33][34] 4 included measures of insulin, [29][30][31]34 and 6 evaluated lipid profile.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Taurine, which is present in octopus and shellfish, is a feedstock of bile and enhances the production rate from cholesterol to bile. Therefore, positive and frequent eating of foods containing these compounds decrease triglyceride and LDL cholesterol levels, consequently preventing arteriosclerosis [17,18].…”
Section: Foods That Decrease the Risk Of Lifestyle Diseasesmentioning
confidence: 99%